Multiscale prediction of thermal conductivity for nanocomposites containing crumpled carbon nanofillers with interfacial characteristics. (8th February 2018) - Kim, Seong Yun; Jang, Han Gyeol; Yang, Cheol-Min; Yang, B.J.
Abstract: The importance of the thermal conductivity of engineering plastics reinforced with nanofillers is increasing in various industries, and the need for a model with which to make reliable predictions continues. We propose a micromechanics-based multiscale model that considers multi-shaped nanofillers to predict the thermal conductivity of composites. The distribution of each phase is assumed to be probabilistically distributed, and the Kapitza resistance at the interface between the filler and matrix was calculated by means of a molecular dynamics simulation. A polybutylene terephthalate (PBT) composite system embedded with multi-walled carbon nanotubes (MWCNTs) was used in a specific simulation. Composites containing MWCNTs of different lengths were also fabricated to obtain appropriate experimental results for the verification of the proposed model. Fourier-transform infrared (FT-IR) spectroscopy, Raman spectroscopy, and field-emission scanning microscopy (FE-SEM) were carried out to confirm that the selected materials could suitably be compared. Finally, the proposed model was applied to the finite element method to examine the heat flux of the composites according to the constitutive properties, and their results were compared to the experimental results.